2017
DOI: 10.3390/molecules22040553
|View full text |Cite
|
Sign up to set email alerts
|

Absorption, Metabolic Stability, and Pharmacokinetics of Ginger Phytochemicals

Abstract: We have previously demonstrated promising anticancer efficacy of orally-fed whole ginger extract (GE) in preclinical prostate models emphasizing the importance of preservation of the natural “milieu”. Essentially, GE primarily includes active ginger phenolics viz., 6-gingerol (6G), 8-gingerol (8G), 10-gingerol (10G), and 6-shogaol (6S). However, the druglikeness properties of active GE phenolics like solubility, stability, and metabolic characteristics are poorly understood. Herein, we determined the physicoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 35 publications
0
39
0
Order By: Relevance
“…However, [10]-gingerol half-life was approximately 2h and maximum plasma concentration was low (estimated at 0.53 ± 0.4 μg/ml, ∼ 1.5 μM), especially due to its diminished amount in the extract. Similarly, Mukkavilli and colleagues [ 27 ] recently reported that [10]-gingerol is stable and suitable for oral administration in mice but that it has poor solubility in plasma and rapid clearance in vivo . Together these studies suggested that tumour inhibition may not be achievable in vivo when [10]-gingerol is administered orally.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, [10]-gingerol half-life was approximately 2h and maximum plasma concentration was low (estimated at 0.53 ± 0.4 μg/ml, ∼ 1.5 μM), especially due to its diminished amount in the extract. Similarly, Mukkavilli and colleagues [ 27 ] recently reported that [10]-gingerol is stable and suitable for oral administration in mice but that it has poor solubility in plasma and rapid clearance in vivo . Together these studies suggested that tumour inhibition may not be achievable in vivo when [10]-gingerol is administered orally.…”
Section: Discussionmentioning
confidence: 99%
“…Given the high tolerability and relatively short half-life of [10]-gingerol (∼2 h) [ 31 ], we are currently investigating whether greater efficacy against established brain metastases could be achieved by increasing the dose and/or frequency of treatment. Moreover, in light of the relatively low plasma concentrations achieved in human or mouse by oral administration (due in part to limited absorption and solubility), greater efficacy of [10]-gingerol against CTCs or disseminated tumour cells could potentially be achieved by improving absorption via better oral formulations and/or by strategies to improve the bioavailability of free [10]-gingerol in plasma as recently proposed [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…This was demonstrated by a study on mice treated with 250 mg/kg of ginger extract. The study monitored the main active components of ginger in the free form, revealing very low seric levels [21]. Also remarkable are the different absorption kinetics observed for each one of the components.…”
Section: Pharmacokinetics From Oral Intakementioning
confidence: 99%
“…Naringin was metabolized to naringenin by human intestinal bacteria (Yu, Jang, Kang, Sung, & Kim, 1997); ginsenoside Rb1 might have been metabolized to bioactive compound(s) by exo-β-D-glucosidase(s) produced from the intestinal bacteria (Jang, Lee, Hyun, & Kim, 2012). Ginger extract included active ginger phenolic compounds: 6-gingerol and 6-shogaol (Mukkavilli et al, 2017). Platycodin D was hydrolyzed rapidly in fecal lysate and decreased by 64% within 30 min (Shan et al, 2015).…”
Section: Screening Of Components In Human Plasmamentioning
confidence: 99%